First-year Students and Organ Donation: A Multidisciplinary Study Conducted in Eastern India Analyzed by Ordinal Regression - Panchali Datta; Sharmistha Bhattacherjee (Indian Journal of Transplantation)
Background: Organ transplantation is becoming increasingly common and established as the preferred treatment for individuals with end-stage organ failure. The global organ transplantation demand–supply gap is greater in Southeast Asia and more so, in India. This study aims to uncover the underlying factors contributing to the disparity between the awareness and willingness for organ transplantation. First-year students possess the potential to function as catalysts for change in their families and society about organ donation, due to their influential role in shaping the future society. Objective: The objective of this study was to evaluate the level of knowledge, attitude, and willingness toward organ donation among first-year students from various fields and to find out their relationship with specific sociodemographic factors. Materials and Methods: The study employed a cross-sectional observational design and included 762 first-year students from several colleges in Eastern India, studying disciplines such as medicine, nursing, engineering, and business. Using Google Forms, a validated and predesigned questionnaire was developed and then sent to participants sharing the QR code. The analysis was conducted using SPSS version 20.0. Results: Among the 762 participants, while 68.6% had a satisfactory to excellent understanding of organ donation, just 5.9% had a positive attitude toward it. Furthermore, if called upon, 21.4% said they would be willing to donate organs. A statistically significant correlation was seen between knowledge, attitude, and the willingness to donate organs. Conclusions: Multiple factors exert influence on organ donation, encompassing elements such as information, cultural views, and individual motivation. Comprehending these components is crucial for developing efficient strategies to promote organ donation.